The pineapple at last - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The Pineapple / Py, C., et al. (1987) In the series 'Techniques agricoles et productions tropicales', Rene Coste (ed.) Maisonneuve & Larose, Paris, 570 pp. Price : 189 FF